The synthesis and analysis of nanodiamond-perylene nanocomposites - Almuhana, Asia (2019)
This dissertation details the synthesis of novel nanodiamond perylene diimide composites. Nanodiamonds were functionalised with perylene diimides via ester bonds using a two step process. Chapter 1 begins with the description of the synthesis and characterisation of PDIs molecules. The synthesis of disubstituted perylene diimides (N,N'-di(5-hydroxypentyl)-1,7-dimorpholinoperylene-3,4:9,10perylenetetracarboxylic diimide (4a) and N,N'-di(5-hydroxypentyl)-1,6- dimorpholinoperylene-3,4:9,10-perylenetetracarboxylic (4b)) and the difficult separation of the 1,6 and 1,7 regioisomers has been undertaken. It has been shown that there is very little difference between the two isomers regarding physical properties and that while introducing small changes in terms of the substituent donating properties have large effects regarding the compounds UV/Vis spectra and thus their colour. 4a has been structurally characterized by single crystal X-ray diffraction, confirming the twisted nature of the central perylene core.